"Twists and Turns": Chief Leabua Jonathan and Cross-Border Collaborations with South Africa, 1965-1976/7 - Twala, Chitja (African historical review, 2024)
Chief Leabua Jonathan's term as prime minister of Lesotho (then Basutoland) began in 1965, the year before the nation's independence from Britain. During his tenure, he remained one of the few regional leaders whose leadership until the end of his term in 1976/7 was marked by a pattern of inconsistency and contradiction towards apartheid South Africa. This article attempts to illuminate the nexus between his relationship with South Africa and the consequences thereof. Furthermore, it discusses how the mid-1960s and late 1970s became a crucial period for his leadership. His prime ministership and the "twists and turns" in his foreign policy vis-à-vis South Africa are discussed. Here the diplomatic role he played within the ambit of "small states theory" and his country's foreign policy is investigated. The article shows how under Jonathan, state politics and regional cross-border struggles and collaborations led to disputes regarding the sovereignty of Lesotho.